Not Your (founding) Fathers' Constitution: Teaching United States Constitutional History - Gerber, Richard A. (The Connecticut Urban Consortium ; New Haven Public Schools, 2007)
Synopsis of the lectures presented during the three-year program, together with a PowerPoint presentations on CD-ROM. This material can be used for preparation of classroom instructional program or directly in the classroom.
Keywords: History; Study and teaching; Study and teaching; Constitutional history; United States. Constitution; United States; United States; dept.his; faculty_collection

When France Was King of Cartography: The Patronage and Production of Maps in Early Modern France - Petto, Christine Marie (Lexington Books, 2007)
When France Was King of Cartography investigates over a thousand maps and nearly two dozen map producers, analyzes the map as a cultural artifact, map producers as a group, and the array of map viewers over the course of two centuries in France. The book focuses on situated knowledge or 'localized' interests reflected in these geographical productions. Through the lens of mapmaking, it examines the relationship between power and the practice of patronage, geography, and commerce in early modern France.
SCSU Faculty Scholar Award
Keywords: 17th century; Cartography; 17th century; Map industry and trade; 18th century; 18th century; Map industry and trade; Cartography; France; History; SCSU Faculty Scholar Award; award_winner; dept.his

Crisis of the Black Intellectual - Wright, W. D. (Third World Press, 2007)
Keywords: African American intellectuals; African Americans; Intellectual life; dept.his; faculty_collection

"I should not be wearing a pilgrim hat": Making an Indian place in urban schools, 1945-75 - Amerman, S. (American Indian Culture and Research Journal, 2007)
2 citations (Crossref) [2023-10-31]
Keywords: dept.his